Issues raised by the selection and introduction of a company informatics system - Reicher, Regina (REGIONAL AND BUSINESS STUDIES, 2011)
In order to ensure long-term success, companies place more emphasis on keeping their existing customers than they do on acquiring new ones. The application of company informatics system solutions makes possible the automatisation and support of this strategy. The introduction of a company informatics system requires significant company resources. It may mean a significant burden both in terms of time and workforce. The success of the introduction is in the interest of all parties; therefore it is necessary that the company start the process of preparation and introduction with great care to avoid failure. The possible issues raised in the phases of this cycle can be grouped according to the viewpoint of the software producer, the distributor, and the company. The analysis and presentation of the reasons for failure can help companies considering implementing informatics system avoid failure. When potential problems are illuminated, they are easier to avoid. I have made a case study with a company and I would like to present my experiences and observations. In my lecture I will present the results of my research, the most frequent issues experienced, their causes and the ways to avoid them.Keywords: company informatics system solutions and processes, anomalies of introduction, objective aspects, support, education, case-study